Contribution And Priority Action Of The Self-Efficacy And Organizational Climate To Improve Innovative Work Behavior - Yuyun Elizabeth Patras; Rais Hidayat; M. Arif Billah (Tadbir : Jurnal Studi Manajemen Pendidikan, 2021)
Innovative work behavior shown by employee activities that generate ideas, promote ideas, and implement ideas is very useful for organizational sustainability. This research seeks to improve innovative work behavior by analyzing the contribution of self-efficacy and organizational climate to ionovative work behavior. The research was conducted on non-permanent instructors at PT PLN (Persero) Pusdiklat with samples 149. Hypothesis testing uses parametric statistical analysis and RCA (Root Cause Analysis) method. The findings of this research: (1) If self-efficacy increases, innovative work behavior will increase; (2) if the organizational climate increases, innovative work behavior will increase; (3) If self-efficacy and organizational climate increase together, innovative work behavior will increase. Based on the RCA  (Root Cause Analysis) method, several priority indicators were found to improve innovative work behavior, namely: forming an innovation team, assigning internships / benchmarks, budgeting for awards, K3L training, creating Knowledge Capturing books, recruiting K3L HR, and book review.